Solid pseudopapillary neoplasm of the pancreas (Frantz tumor) in a 14-year-old girl - Teerin T. Meckmongkol; Erica Polleto; Harsh Grewal (Elsevier, 2018)
We report the case of a 14-year old female who presented with a two day history of abdominal pain. A contrast enhanced computed tomography (CT) of the abdomen and pelvis demonstrated a characteristic solid-cystic mass in the pancreatic tail which was concerning for a solid pseudopapillary neoplasm (SPN) of the pancreas. The patient underwent an uneventful laparoscopic subtotal pancreatectomy with splenic preservation. We have shown that laparoscopic pancreatic resection with splenic preservation can be performed safely for SPN in a child. We also used two techniques that are useful to accomplish this safely- [1] lateral to medial dissection which assists in the identification of the splenic vein and artery, and [2] slow staple compression of the pancreas which may decrease pancreatic leak rates. Keywords: Solid pseudopapillary neoplasm of the pancreas, Frantz tumor, Pancreatic tumor, Laparoscopy pancreatectomy, Splenic preservation